Possible association between high social anxiety level and genetic markers in young adult Internet addicts. (1st June 2022) - Trusova, A.; Gvozdetckii, A.; Merkulova, T.; Chuprova, N.; Solovieva, M.; Grechany, S.; Soldatkin, V.; Yakovlev, A.; Ponizovsky, P.; Iluyk, R.; Egorov, A.; Krupitsky, E.; et al.
Abstract : Introduction: Internet addiction (IA) is a rapidly growing disorder especially among adolescents and young adults. Social anxiety is one of the risk factors for IA. Also, genes involved in dopaminergic and serotoninergic systems are among the candidate genes most frequently associated with IA. Objectives: The study aimed to investigate the association between social anxiety level and genetic markers in young adult Internet addicts. Methods: IA group included 44 people (Chen/Chinese Internet Addiction Scale (CIAS) score ≥ 65), 75, 0% males), the average age 22, 0 [18, 0;25, 0] y.o. (Md [Q1; Q3]). Healthy control group (CIAS score was less 65) included 120 people, (73, 3% males), the average age 23, 0 [22, 0;24, 0] y.o. Psychometric measures: Liebowitz Social Anxiety Scale (LSAS). Genetic markers: rs2072450 in GRIN2A, rs2832407 in GRiK-GluR5, HUMTH01 in TH01 (S<9, L>=9 repeats). The impact of genotypes on social anxiety scores was identified using Proportional Odd Logit modeling taking into account group affiliation. Results: Group of IA reported significantly higher levels in almost all LSAS measures including total score. We found that carriers of the genotypes rs2072450 CC (p=0.004 vs.CA/AA), rs2832407 CC (p=0.023 vs AA), and TH01 SS (p=0.013 vs. LL) scored significantly higher of LSAS total in the IA group. There were no significant differences in the healthy controls group. Conclusions: The rs2072450(CC) in GRIN2A, rs2832407(CC) in GRiK-GluR5, and HUMTH01 in TH01 (SS) genotypes may be possibly associated with higher social anxiety levels in Internet addicts. Disclosure: The study was supported by the Russian Foundation for Basic Research (RFBR), project #18-29-22079.